Analysing the role of psychosocial factors on seafarers' mental health post-covid-19 and beyond - Lai, Daniel Wei Jie (Nanyang Technological University, 2023)
Purpose – This research focuses on the psychosocial impacts of working in the seafaring sector. Traits like self-understanding, social interactions, and mental processes that sustain links between the individual and their social surroundings are the subject of psychosocial theories. Learning more about the challenges seafarers encounter will shed light on their effect on seafarers’ mental health. For this paper, four factors affecting mental health were highlighted: onboard peer support, psychological capital, fatigue, and burnout.